Finnish deposit banks 1980-1993: years of rapid growth and crisis - Heikki Koskenkylä; Jukka Vesala (Bank of Finland, 1994)
This study investigates the growth of Finnish deposit banks over the period 1980-1993.We examine the growth in balance sheets, lending and deposits of the public as well as major changes in the balance sheet structure.The focus of the study is first on the overall banking industry and second on the commercial, savings and cooperative banks as groups, including a separate treatment of the largest commercial banks.The study ends with a brief comparison of the Nordic countries.Also included is a discussion of changes that have occurred in the banking environment, but the emphasis is on the effects of bank-specific microeconomic factors on the rapid acceleration in the growth of bank lending and on the heating up of competition for market share, which took place after lending rates were deregulated and foreign exchange regulations eased.The micro factors examined are the change in banks' risk profile during the period of rapid growth as well as the various incentives behind the growth and competition for market share.To be sure, changes in the banking environment and macroeconomic developments have played a role in fomenting the banks' profitability crisis in the beginning of the 1990s, but the main reasons for the crisis can be found in the banks' strategic choices.
URN:NBN:fi:bof-20140807312
Keywords: 330